Organic carbon fluxes of a glacier surface: A case study of Foxfonna, a small Arctic glacier. Issue 2 (21st October 2018) - Koziol, Krystyna A.; Moggridge, Helen L.; Cook, Joseph M.; Hodson, Andy J.
Abstract: Arctic glaciers are rapidly responding to global warming by releasing organic carbon (OC) to downstream ecosystems. The glacier surface is arguably the most biologically active and biodiverse glacial habitat and therefore the site of important OC transformation and storage, although rates and magnitudes are poorly constrained. In this paper, we present measurements of OC fluxes associated with atmospheric deposition, ice melt, biological growth, fluvial transport and storage (in superimposed ice and cryoconite debris) for a supraglacial catchment on Foxfonna glacier, Svalbard (Norway), across two consecutive years. We found that in general atmospheric OC input (averaging 0.63 ± 0.25 Mg a ‐1 total organic carbon, i.e. TOC, and 0.40 ± 0.22 Mg a ‐1 dissolved organic carbon, i.e. DOC) exceeded fluvial OC export (0.46 ± 0.04 Mg a ‐1 TOC and 0.36 ± 0.03 Mg a ‐1 DOC). Early in the summer, OC was mobilised in snowmelt but its release was delayed by temporary storage in superimposed ice on the glacier surface. This delayed the export of 28.5% of the TOC in runoff. Biological production in cryoconite deposits was a negligible potential source of OC to runoff, while englacial ice melt was far more important on account of the glacier's negative ice mass balance (–0.89 and –0.42 m a ‐1 in 2011 and 2012, respectively). However, construction of a detailed OC budget using these fluxes shows an excess of inputs over outputs, resulting in a net retention of OC on the glacier surface at a rate that would require c . 3 years to account for the OC stored as cryoconite debris. © 2018 John Wiley & Sons, Ltd. Abstract : Quantifying organic carbon (OC) fluxes on a shrinking Arctic glacier surface resulted in net accumulation. The main inputs of this OC are atmospheric deposition and ice melt. Both the particulate and dissolved OC are removed from glacier surfaces with a delay, facilitating surface darkening and a late‐summer release of labile OC.